2022
DOI: 10.1590/s2175-97902022e20639
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of some vital trace elements in patients with acute pancreatitis: A case-control study

Abstract: Trace elements have an important influence on the living system and play a major role in a variety of processes necessary for life. This case study was conducted as an attempt to expand our knowledge of the relationship between trace elements and their effect on acute pancreatitis. Sixty-five patients diagnosed with acute pancreatitis with mean age 43.6 years, along with sixtyfive healthy volunteers with a mean age 45.7 years, were included in this study. The obtained results indicated a significant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These authors postulated that oxidative stress caused by cancer development and progression oxidizes the sulfhydryl groups in cysteine, decreasing the Zn-binding capacity with a consequent higher amount of free Zn that is rapidly eliminated through urine. Conflictingly, other authors reported decreased levels of Zn in subjects with acute pancreatitis and pancreatic cancer, or in rats with induced pancreatitis [14,25,43]. In addition, it was observed that the Zn concentration in pancreatic fluid was comparable in patients with chronic pancreatitis and pancreatic cancer compared to a normal pancreas [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These authors postulated that oxidative stress caused by cancer development and progression oxidizes the sulfhydryl groups in cysteine, decreasing the Zn-binding capacity with a consequent higher amount of free Zn that is rapidly eliminated through urine. Conflictingly, other authors reported decreased levels of Zn in subjects with acute pancreatitis and pancreatic cancer, or in rats with induced pancreatitis [14,25,43]. In addition, it was observed that the Zn concentration in pancreatic fluid was comparable in patients with chronic pancreatitis and pancreatic cancer compared to a normal pancreas [47].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Cr ions may activate Fenton-like reactions, generate hydroxy radicals that induce oxidative stress, activate transcription factors such as nuclear factor kappa B (NF-κB), activate protein-1 (AP-1), tumor protein P53 (p53) and hypoxia-inducible factor-1 (HIF-1), regulate the cell cycle and induce apoptosis [ 23 , 24 ]. In previous literature, a study reported a high level of Cr in the serum of subjects with acute pancreatitis [ 25 ]. In addition, significantly increased levels of Cr in pancreatic juice were quantified in three population groups, and the levels of Cr followed a decreasing order: pancreatic cancer > pancreatitis > controls [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ni may cause biochemical changes such as iron resorption leading to anemia. Ni also interrupts calcium usage by bone, resulting in parakeratosis damage or interfering with zinc metabolism [7]. Ni prompts embryo noxious and nephrotoxic effects, sensitized reactions, and contact dermatitis [8], while Ni deficiency particularly affects carbohydrate metabolism [9].…”
Section: Introductionmentioning
confidence: 99%